Zinc in Soils and Plants 1993
DOI: 10.1007/978-94-011-0878-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Uptake from Soils

Abstract: Characterizing zinc availability by soil testing provides important information on the pool size of zinc potentially available for uptake. Concentrations of zinc in soil solution, particularly at high soil pH, however, are very low and mobility and transport to the root surface are usually rate limiting factors of soil supply. Utilization of potentially available zinc is thus mainly or exclusively confined to rhizosphere soil. Root-induced changes in the rhizosphere are of particular imporatance for zinc uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(99 citation statements)
references
References 90 publications
4
91
0
4
Order By: Relevance
“…As it was observed before, the extractable Zn in soils had not decreased at all, or only slightly at high P supply (Warnock 1970, Marschner 1993). In our former greenhouse experiment (Kremper and Seres 2010) we also observed that Zn deficiency occurred even at high extracted Zn content when The effect of treatments on the yield elements of maize.…”
Section: Resultssupporting
confidence: 63%
“…As it was observed before, the extractable Zn in soils had not decreased at all, or only slightly at high P supply (Warnock 1970, Marschner 1993). In our former greenhouse experiment (Kremper and Seres 2010) we also observed that Zn deficiency occurred even at high extracted Zn content when The effect of treatments on the yield elements of maize.…”
Section: Resultssupporting
confidence: 63%
“…In the plots with added N, we can attribute the greater availability of Zn to the decrease in soil pH as a consequence of N-fertilization. The concentrations of Zn in solution are inversely related to soil pH (Marschner 1993) and the sorption of Zn in clay soils increases rapidly above a pH of 5 (Cavallaro and McBride 1984). The decrease in soil pH of half a unit in the plots with added N (from 5.4 to 4.9) appears to have been sufficient to mobilize extra Zn.…”
Section: Calcium Magnesium and Zincmentioning
confidence: 93%
“…Zinc fertilization, e.g. applied as zinc sulphate (ZnSO 4 ), is an effective method to increase Zn plant uptake, but its effect is often of short duration, especially on calcareous soils (Marschner 1993). Similarly, decreasing pH, e.g.…”
Section: Research Articlementioning
confidence: 99%